(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
The teaching internship aims to enable the graduate student to act as a teacher. The aim of this study was to evaluate the learning conditions of behavior analysts promoted by the teaching internship of master’s and doctoral programs in Brazil. A questionnaire was applied to 78 students and graduates of master’s and doctoral programs with a focus on Behavior Analysis at 11 institutions. It was identified that students have opportunities to carry out activities related to teaching, but with a low frequency of guidance and feedback from the advisor. Of the activities carried out in the internship, those performed less frequently were discipline planning and assessment preparation. On the other hand, correction of works was performed more frequently. Given the conditions for learning the teaching repertoire, it is possible to conclude that the teaching internship has been an insufficient opportunity to improve their teaching repertoire in Behavior Analysis graduate students.